2019
DOI: 10.9734/cjast/2019/v37i230275
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Safety and Health Management Systems and Their Compliance among Petrol Stations in Kenya: A Case Study in Nakuru County

Abstract: Companies have a legal and social responsibility to ensure the safety of its workers, all persons lawfully present at the workplace and the surrounding community. This requires laid down procedures and routing process which aims at identifying, eliminating, minimizing and control the work-related hazards and decrease the risks. To be effective, the Occupational Safety and Health Management Systems (OSHMS) need to be integrated within the organization’s safety policy and objectives. Therefore, this explains why… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 7 publications
2
10
0
Order By: Relevance
“…Working hours showed 64% of the respondents worked for 8-10 hours per day, 23% for 6-8 hours, and 13% worked for 10 hours during their shifts. The findings are in line with those of the study conducted by Mutungi et al (2019), which found that 86.7% of employees worked between 8-10 hours with some 5.6% working for more than 10 hours. Working for more than 8 hours could lead to accidents in the workplace, especially because workers are fatigued and concentration levels are low.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Working hours showed 64% of the respondents worked for 8-10 hours per day, 23% for 6-8 hours, and 13% worked for 10 hours during their shifts. The findings are in line with those of the study conducted by Mutungi et al (2019), which found that 86.7% of employees worked between 8-10 hours with some 5.6% working for more than 10 hours. Working for more than 8 hours could lead to accidents in the workplace, especially because workers are fatigued and concentration levels are low.…”
Section: Resultssupporting
confidence: 92%
“…Concerning routine work practices, 97.2% of employees agreed to utilizing personal protective equipment (PPE) while performing their tasks. Only 60.0% and 71.4% of the respondents used PPE in the studies conducted by Mutungi et al (2019) and Okafoagu et al (2017) respectively. The majority of the respondents (72.2%) were able to use fire extinguishers and even in the study conducted by Kakwi (2020), results indicated many (99.1%) participants were able to use fire extinguishers.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations